## Expanding (x-11)^2 into a Trinomial in Standard Form

The expression (x-11)^2 represents the square of a binomial. To expand it into a trinomial in standard form, we can use the FOIL method or the pattern for squaring a binomial.

### Using FOIL Method

**F**irst: x * x = x^2
**O**uter: x * -11 = -11x
**I**nner: -11 * x = -11x
**L**ast: -11 * -11 = 121

Adding all the terms together, we get:

x^2 - 11x - 11x + 121

Combining like terms, the final trinomial in standard form is:

**x^2 - 22x + 121**

### Using the Pattern for Squaring a Binomial

The pattern for squaring a binomial is:

(a - b)^2 = a^2 - 2ab + b^2

In our case, a = x and b = 11.

Substituting these values into the pattern, we get:

x^2 - 2(x)(11) + 11^2

Simplifying the expression gives us:

**x^2 - 22x + 121**

Both methods yield the same result, confirming that (x-11)^2 expanded as a trinomial in standard form is **x^2 - 22x + 121**.